Improving The Students Vocabulary By Using The Suggestopedia Media At 4th Graders Of Pacarmulyo 1 Elementary School - Nurngaeni, Hikmah; Purwanto, Buntara Adi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the suggestopedia media in improving students' English vocabulary at Pacarmulyo 1 Elementary School which is located in Jetis Pacarmulyo Village, Wonosobo. The researcher has to visit and observe the school to identify problems related to this research. Researchers used the Suggestopedia method media to overcome students' problems in enriching English vocabulary using a classroom action research (CAR) design. This research consists of 2 cycles, each cycle has stages, namely planning, implementation, observation and reflection. The sample taken forth is research was class IV. The research instrument are: interviews, observations, test results and documentation. The results of observations and tests increased. Observation results, in cycle 1 it was 56% and in cycle 2 it was 84%. Then the test results in the pre-cycle were 34.1%, in cycle 1 it was 56.9% and in cycle 2 it was 79.3%. The results of the interview test also changed, from the students who did not like English lessons became like after using this method. From the result so obtained by researchers, it can be concluded that using the Suggestopedia method media can improve students' ability to enrich their English vocabulary